MicroRNA-145 inhibits hepatic stellate cell activation and proliferation by targeting ZEB2 through Wnt/β-catenin pathway. (July 2016) - Zhou, Dan-dan; Wang, Xiao; Wang, Yang; Xiang, Xin-jian; Liang, Zi-cong; Zhou, Yi; Xu, Ang; Bi, Cheng-hao; Zhang, Lei
Graphical abstract: Highlights: MiR-145 is down-regulated in liver fibrosis and over-expression of miR-145 inhibits activation and proliferation of HSCs. ZEB2 is up-regulated in liver fibrosis and knock down of ZEB2 can also suppress the process of HSCs activation and proliferation. The anti-fibrosis mechanism of miR-145 is partly through Wnt/β-catenin signaling by targeting ZEB2. Abstract: The activation of hepatic stellates cells (HSCs) is well believed to play a pivotal role in the development of liver fibrosis. MicroRNA-145 (miR-145) is known to suppress the progression of hepatocellular carcinoma, and is previously reported to be associated with Wnt/β-catenin pathway, but its role in the progression of hepatic fibrosis and activation of HSCs remains unknown and is warranted for investigation. In the present study, we found that the expression of miR-145 is significantly down-regulated in vivo in CCl4 -induced mice liver fibrosis as well as in transforming growth factor-β1 (TGF-β1) induced HSC-T6 cell lines and human hepatic stellate cell line LX-2 in vitro . Furthermore, over-expression of miR-145 inhibited TGF-β1-induced the activation and proliferation of HSC-T6 cells in vitro . Mechanistically, we identified that zinc finger E-box-binding homeobox 2 (ZEB2), a key mediator of epithelial-to-mesenchymal transition, acted as a functional downstream target for miR-145. Interestingly, ZEB2 was shown to be involved in the TGF-β1-induced HSCs activation by regulating Wnt/β-catenin signaling pathway. Taken together, our results revealed the critical regulatory role of miR-145 in HSCs activation and implied miR-145 as a potential candidate for therapy of hepatic fibrosis by regulation of Wnt/β-catenin through targeting ZEB2.